STUDYING OF FORMATION OF PATRIOTIC QUALITIES OF STUDENTS OF A TECHNICAL HIGHER EDUCATION INSTITUTE - Nadezhda E. Larushkina; Ekaterina S. Larushkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the article a relevant problem of developing of patriotic qualities of students of a technical higher education institute, the formation of their spiritual and moral positions, and patriotism is considered. The analysis of results of survey among students is carried out.The list of the most expedient educational tools of patriotic qualities is provided.